(untitled) (Avaliação: Revista da Avaliação da Educação Superior, 2014)
This study aims to locate the subjective thinking between students physical education trainees during teaching practice. Set in the format of the study and interpretation of a descriptive nature, can contribute to a better understanding and interpretation of the repertoire of experiential trainees Physical Education. The instrument used consisted of question relating to the quantitative and qualitative analysis and focused on five dimensions: Social and Emotional Aspects; Vocational Aspects; Learning and Professional Development; Supervision; Professional and Institutional Socialization. The sample consisted of 118 trainees, from two higher education institutions, one private and one public. The personal growth associated with the placement experience focuses on aspects related to professional competence. The professional skills of the stage are directly related to the organization and management of teaching and learning.